Peran Konsep Diri Dan Dukungan Sosial Terhadap Depresi Pada Penderita Gagal Ginjal Yang Menjalani Terapi Hemodialisis - Azahra, Mega (EMPATHY Jurnal Fakultas Psikologi, 2013)
Abstact This research aimed to determine the role of Self-Concept and Social Support on Depression in Patients Kidney Disease with Hemodialysis Therapy. The Subjects of this research were 60 patients kidney disease with hemodialysis therapy at PKU Mumammadiyah Yogyakarta Hospital. The data collection tools of this research used the The Beck Depression Inventory (BDI) Scale, the Self-Concept Scale, and the Social Support Scale. Analysis of the statistical method of multiple regression analysis using SPSS 17 for windows. The results of research showed : (1) The Role of Self-Concept and Social Support on Depression in Patients Kidney Disease with Hemodialysis Therapy with R = 0.616 and a value of F = 17.400 with p = 0.000 (p <0.01), (2) The existence of a negative role self-concept of the depression to the value t = -2.957 and p = 0.005 (p <0.01), (3) the negative role of social support on depression with the value t = -3.820 and p = 0.000 (p <0.01). Keyword: Self Concept, Social Support, Depression